Assessment of factor affecting performance of undergraduate medical students at GMERS medical college, Dharpur-Patan, North Gujarat, India: a cross sectional and descriptive study - Amaliyar, Jatinkumar; Modi, Krunal (International Journal Of Community Medicine And Public Health, 2019)
Background: Undergraduate medical education in India and many developing nations is facing new challenges today. Multiple stressors including academic burden, parental pressure and even psychological ailments affect medical students. Depression, burnout and stress are commonly seen in medical students. This increases psychiatric morbidity and affects performance. This study was conducted to extract the factors which are important factors for the effective learning of students and influences their performance during curriculum. Methods: This cross sectional and descriptive study was carried out among 100 MBBS student of 2015 of GMERS medical college, Dharpur-Patan during March to April 2018. Students were administered pre-designed and structured questionnaire after obtaining their informed consent while seated in the lecture hall. Responses of questionnaires were analyzed with Epi Info 7.0 and MS Excel. Frequencies and percentages were calculated and Chi-square test was applied to find out significance. Results: Most important factors which were affecting students’ performance in our study were language problems, competent teachers, social media and campus environment. 70% students have no issue with financial status. Majority students prefer self study. Conclusions: Identification of hidden factors affecting academic performance is very important in very early stage so they can perform better in their study in future. Language, hostel environment, teachers’ attitude towards students etc are also certain important factors which help students to perform better in curriculum.